CONCEPTIONS OF LEARNING THROUGH LEARNING STYLES AND COGNITIVE DIMENSION IN VOCATIONAL EDUCATION - Mohamad, Mimi Mohaffyza Binti; Mei Heong, Yee; Tze Kiong, Tee (Journal of Technical Education and Training, 2014)
Individual learning preferences and learning styles have been defined in several different ways according to theoretical models. In the context of vocational education, students have different characteristics compared to their counterparts in other fields of education, since learning orientation is more on job focused. However, the cognitive dimension is still need to be measured especially for learners at school level. This article addresses the relationship between learning styles and cognitive dimension in vocational education at secondary school level. Based on the Felder-Silverman Learning Styles and Cognitive Dimension Model, the authors highlighted students’ dimension of learning styles, students’ preferences on learning preference, and the conceptual of knowledge, skills and problem solving construct according to taxonomy. It is concluded that the vocational students are more incline to be visual learner. This learning preference and learning styles will contribute to their engagement on the concept of learning in vocational education.